2019
DOI: 10.18093/0869-0189-2019-29-3-302-310
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized, double-blind, placebo-controlled clinical trial in adult patients with acute respiratory viral infection

Abstract: The aim of this study was to investigate efficacy and safety of released-active antibodies against interferon-gamma, CD4-receptor, and histamine in adult patients with acute respiratory viral infection (ARVI).Methods. This multicenter, randomized, double-blind, placebo-controlled clinical trial in parallel groups was carried out in 2011 – 2012. Data of 161 ambulatory patients from 4 centers at Russian Federation were included in the analysis. The patients' age was 18 to 60 years. Patients with ARVI signs durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…From day 2 through 5, a tablet was administered three times daily. e efficacy and safety of this specific drug regimen have been assessed and proven in previous RCTs [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…From day 2 through 5, a tablet was administered three times daily. e efficacy and safety of this specific drug regimen have been assessed and proven in previous RCTs [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Treatmentmentioning
confidence: 99%
“…A range of randomized controlled trials (RCTs) have shown the efficacy and safety of Ergoferon in the treatment of adult and children with influenza and vARIs [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The active pharmaceutical ingredients (released-active dilutions of antibodies) are produced by GMP manufacturing facilities in Russia. Clinical studies on Ergoferon (Anon, 2019b,c;Sel'kova et al, 2019;Geppe et al, 2019;Kondyurina et al, 2016a,b), as well as other released-active drugs (Anon, 2019d,e), have been conducted in accordance with GCP and they are controlled by the Ministry of Health of the Russian Federation. Detailed information about the drug Ergoferon is available on the official website of the Ministry of Health (Anon, 2019f).…”
mentioning
confidence: 99%